2017
DOI: 10.1017/s0029665117001434
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dietary meat intake reduction on haematological parameters in healthy adults

Abstract: Meat is a rich source of dietary protein, fatty acids and micronutrients (1) many of which are involved in the process of blood cell production. In the UK, meat and meat products contribute up to 40 % and 37 % of average daily protein consumed by males and females respectively (2) . However, epidemiological studies have indicated an association between red and processed meat intake and an increased risk of developing cardiovascular disease (3) and certain cancers (4) , and people are being advised to reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…On the other hand, in line with previous literature ( Ali et al, 2017 ; Azadbakht and Esmaillzadeh, 2009 ; Chai et al, 2017 ; Ley et al, 2014 ), we observed positive associations with SCI biomarkers and (i) consumption of food groups that are abundant in unhealthy diets (such as processed and unprocessed red meat) and (ii) adherence to Western-style diets ( Khayyatzadeh et al, 2018 ; Silveira et al, 2018 ). It is well known that unhealthy diets are characterised by higher consumption of sugar, salt, refined grains and saturated- and trans-fatty acids ( Jacka, 2017 ; Marx et al, 2017 ) and, of special importance, saturated fatty acids, have been repeatedly shown to increase inflammatory markers ( Mu et al., 2014 ; Ruiz-Núñez et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, in line with previous literature ( Ali et al, 2017 ; Azadbakht and Esmaillzadeh, 2009 ; Chai et al, 2017 ; Ley et al, 2014 ), we observed positive associations with SCI biomarkers and (i) consumption of food groups that are abundant in unhealthy diets (such as processed and unprocessed red meat) and (ii) adherence to Western-style diets ( Khayyatzadeh et al, 2018 ; Silveira et al, 2018 ). It is well known that unhealthy diets are characterised by higher consumption of sugar, salt, refined grains and saturated- and trans-fatty acids ( Jacka, 2017 ; Marx et al, 2017 ) and, of special importance, saturated fatty acids, have been repeatedly shown to increase inflammatory markers ( Mu et al., 2014 ; Ruiz-Núñez et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…Providing US and UK participants with meat substitutes, recipes, and educational materials led to large reductions in meat consumption (13): a 40% reduction in red and processed meat (31), a 54% reduction in spending on meat (32), and a 70% reduction in meat consumed (33). These results are impressive but, unlike increasing vegetarian availability, are time-and resource-intensive; thus, they may not be scalable, and their effects can diminish over time (24,31). One paper found that meat consumption was 60% lower at the end of the intervention than at the baseline but that after 2 mo, the effect had decreased to 40% (31).…”
Section: Discussionmentioning
confidence: 99%
“…These results are impressive but, unlike increasing vegetarian availability, are time-and resource-intensive; thus, they may not be scalable, and their effects can diminish over time (24,31). One paper found that meat consumption was 60% lower at the end of the intervention than at the baseline but that after 2 mo, the effect had decreased to 40% (31). Reducing the serving size of meat portions reduced meat consumption by 13 to 14% (34,35); hence, increasing vegetarian availability combined with smaller meat portions could be a powerful combined strategy to reduce the mass of meat served by cafeterias.…”
Section: Discussionmentioning
confidence: 99%